2017
DOI: 10.3390/ijms18071429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Solvents on Microalgae Growth, Metabolism and Industrial Bioproduct Extraction: A Review

Abstract: In this review, the effect of organic solvents on microalgae cultures from molecular to industrial scale is presented. Traditional organic solvents and solvents of new generation-ionic liquids (ILs), are considered. Alterations in microalgal cell metabolism and synthesis of target products (pigments, proteins, lipids), as a result of exposure to organic solvents, are summarized. Applications of organic solvents as a carbon source for microalgal growth and production of target molecules are discussed. Possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 185 publications
(341 reference statements)
2
30
0
1
Order By: Relevance
“…These survival strategies stimulate the growth of green algae if allelochemical concentrations are below a certain threshold. Additionally, some organic solvents were reported to affect algal growth in both inhibiting and stimulating manners depending on different concentrations and algae [47]. Therefore, there might be a potential effect of methanol on our results.…”
Section: Discussionmentioning
confidence: 88%
“…These survival strategies stimulate the growth of green algae if allelochemical concentrations are below a certain threshold. Additionally, some organic solvents were reported to affect algal growth in both inhibiting and stimulating manners depending on different concentrations and algae [47]. Therefore, there might be a potential effect of methanol on our results.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, turbidity of the liquid medium was not a limiting factor for nutrients removal under the working conditions investigated since CO 2 was widely available for microalgal growth. Furthermore, the influence of the presence of ethanol in the cultivation medium on nutrients removal was also negligible under the concentrations tested (1725 ± 32 mg L −1 and 852 ± 65 mg L −1 in D1/5 and D1/10 wileyonlinelibrary.com/jctb 27 showed that, in general terms, microalgal growth is not inhibited up to ethanol concentrations of 3000 mg L −1 . In this context, air supply has been proposed as a strategy to enhance nutrients removal from centrates or other nutrient-rich effluents in microalgal-bacterial photobioreactors.…”
Section: Depletionmentioning
confidence: 93%
“…Examples of such carotenoids which are widely used in pharmaceutical and food industries as nutritive supplements and coloring agents are β-carotene and astaxanthin that are mainly extracted from D. salina and Haematococcus pluvialis, respectively [115,116]. The use of 1-ethyl-3-methylimidazolium dibutylphosphate for the extraction of astaxanthin from H. pluvialis certainly aids the industry in fulfilling the need of the market via vastly improving the extraction yield at a lower energy demand and production cost which in turn makes the product to be more competitive even with the presence of artificially synthesized astaxanthin in the market [117,118]. Other microalgae metabolites of interest include tocopherols, phenolics compounds, flavonoids, and vitamins that have been previously found in microalgae extracts of different species and may be potentially extracted using ILs [119][120][121].…”
Section: Bioactive Compoundsmentioning
confidence: 99%